2015
DOI: 10.1007/s13233-015-3104-3
|View full text |Cite
|
Sign up to set email alerts
|

Norbornene end-capped polyimide for low CTE and low residual stress with changes in the diamine linkages

Abstract: The effects of norbornene (NE) crosslinking and diamine bridge linkages (ether, sulfone, and trifluoromethyl) on polyimide films were investigated. The purpose of this study was to study the behavior of the NE endcapped polyimide with different diamine bridge linkage structure at elevated temperatures on residual stress and modulus change. 5-Norbornene-2,3-dicarboxylic acid was introduced as the end-capping agent in order to increase the ratio of crosslinking in the structure through reverse Diels-Alder reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…22,23 A few studies have been involved to look for the ways to decrease the CTE values of PIs. 24 26 In this work, we found that CTE was influenced by the chain rigidity and the existence of –CN groups. For each series, the PMDA-based PI had the lowest CTE value, and the one from 6FDA had highest CTE.…”
Section: Resultsmentioning
confidence: 63%
“…22,23 A few studies have been involved to look for the ways to decrease the CTE values of PIs. 24 26 In this work, we found that CTE was influenced by the chain rigidity and the existence of –CN groups. For each series, the PMDA-based PI had the lowest CTE value, and the one from 6FDA had highest CTE.…”
Section: Resultsmentioning
confidence: 63%
“…The modulus and CTE play a leading role in determining the shrinkage behavior of epoxy resins. Therefore, cyclic stress is a function of the CTE and modulus of the film with temperature 33 . The stress values obtained by using the theoretical calculation equations from the modulus, CTE, and T g are also listed in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Although the exact mechanism of CTE is uncertain and controversial, 40 many works also reported that the value of CTE decreases with the development of intra-chain rigidity. [41][42][43] In our previous work, 44 we raised the possible mechanism of negative CTE on b-H-H-APA+PMDA PI. And now, for b-H-MeO-APA+PMDA PI, its CTE value is also negative, which further confirming that the thermal shrinkage behavior in the in-plane direction is possibly an essential feature for b-H-H(MeO)-APA+ PMDA PIs.…”
Section: Thermal and Mechanical Properties Of B-h-meo-apis Filmsmentioning
confidence: 99%